KAJIAN SISTEM WAYFINDING DI JALAN ASIA AFRIKA BANDUNG - Sally Octaviana Sari; Enok Sugiharti; Sekar Septiani (Jurnal Arsitektur ARCADE, 2024)
Abstract: Wayfinding is collecting information, determining and making decision about where to go and move through a space through mental map and object recognition (Dharmawan et al, 2021; Ninda H et al, 2020). The significance criteria of the wayfinding system are safety, a pleasant spatial experience and impact of commercial of a land value, the possibility for people returning back and how long they spending time in a public space (Symonds, 2018). Asia Afrika street  is the anchor for people’s activities in Bandung City. In unfamiliar space, we often faced the problem finding the destination. Particulary if the urban space is relatively hard to understand and legitimate due to unidentified as a distinctive character. This research aims to find out the knowledge of user’s wayfinding patterns when exploring Asia Afrika’s public open space by using a qualitative-exploratory approach. Data were collected by survey, observation, interview and identifying wayfinding objects along the research location.  Data was analyzed by using content analysis. Hopefully, this result  contributes  to urban planning in determining wayfinding elements,  imageable streetscape and accesible  for all users (walkable). Keyword: Wayfinding, walkable space, mental mapAbstrak: Wayfinding adalah proses pengumpulan data, penentuan dan pembuatan keputusan arah bergerak dalam suatu ruang melalui peta mental dan pengenalan objek (Dharmawan et al, 2021; Ninda H et al, 2020). Signifikansi kriteria sistem wayfinding adalah keselamatan, pengalaman spasial yang menyenangkan dan dampak komersial nilai lahan di suatu ruang publik (Symonds, 2018). Jalan Asia Afrika merupakan salah satu pusat aktivitas di Kota Bandung. Di ruang non familiar, manusia seringkali mengalami kesulitan dalam menemukan tujuan. Khususnyadi ruang publik yang relatif sulit dimengerti dan diidentifikasi karena karakternya yang berbeda. Penelitian ini bertujuan untuk  untuk menemukan pengetahuan tentang pola wayfinding ketika mengeksplorasi ruang di Jalan Asia Afrika melalui pendekatan kualitatif – eksploratif. Pengumpulan data dilakukan melalui survey, observasi dan wawancara serta identifikasi objek – objek wayfinding di sepanjang lokasi penelitian. Data dianalisis dengan menggunakan analisis isi. Penelitian ini diharapkan dapat memberikan kontribusi dalam perencanaan elemen wayfinding, bentang jalan (streetscape) yang mudah dikenali,  aksesibel dan walkable untuk semua pengguna.Kata Kunci: wayfinding, ruang walkable, peta mental